RESPON MASYARAKAT SAGERAT TERHADAP KEBERADAAN PASAR PINASUNGKULAN KOTA BITUNG - Ronald H. Mamongan; Ventje V. Rantung; Ribka M. Kumaat; Jean J. F. Timban (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine the response of Sagerat commnuity towartd the existence of Pinasungkulan Market at Bitung City. The determination of the sample is determined by accidental sampling technique. The data used are primary data and secondary data. Primary data was obtained by questionnaires filled by community members as respondents of this study who are live around the market. The research used Likert Scale method. Secondary data obtained from Market Office and Market Management Agency Pinasungkulan at Bitung City. Data analysis in this study used descriptive analysis based on the answers that given in the questionnaire respondents. The result of the research shows that from 4 variables which is measured Pinasungkulan market is pleased by the sorrounding community; it can be seen from the total number of scores obtained in 3,815, where in the scale of measuring the variable number of score 2801-4200, means the market is pleased by its the surrounding community.